Comprehensive pediatric care of rare bleeding disorders. Issue 2 (April 2010) - Giansily-Blaizot, Muriel; Schved, Jean-François
Although less common than hemophilia or von Willebrand disease, inherited rare bleeding disorders, comprising afibrinogenemia and deficiencies in factors II, V, VII, X, XI, XIII or V plus VIII combined, or in vitamin K-dependent coagulation factors, may lead to severe bleeding episodes such as recurrent hemarthroses and neonatal intracranial or gastrointestinal hemorrhage. Consanguinity significantly increases the risk of the occurrence of all rare bleeding disorders that are associated with an autosomal recessive pattern of inheritance. Each of the disorders is characterized by a wide interindividual variation in clinical phenotype and a large mutational spectrum with no clear correlation between the phenotype and genotype. Replacement therapy relies on specific molecules or concentrates (afibrinogenemia, factor VII, XI and XIII deficiencies), on a mixture of different concentrates that are otherwise known as a prothrombin complex, which contains factors II, VII, IX and X, or on fresh frozen plasma. International consensus guidelines for treatment modalities are progressing; however, guidelines for prophylaxis, especially in pediatric patients, are lacking.